Pengembangan Multimedia Interaktif Tematik Berbasis Powerpoint di Sekolah Dasar - Rengganis, Diah Ayu; Ain, Siti Quratul (Institut Agama Islam Sunan Giri (INSURI) Ponorogo, 2022)
This development research was carried out because there are still many teachers who have not been able to use technology as a learning medium to make students less interested in the material taught by the teacher. This research aims to develop Powerpoint-based interactive multimedia that utilizes technology and its creation and implementation. This research was conducted at SDN 010 Kuantan Sako, which is intended for a fifth-grade elementary school. This is an ADDIE development research (Analysis, design, development, implementation, evaluation). Still, due to limited time, energy, and costs, the researchers only did it until the Development stage, not proceeding to the Implementation and Evaluation stages. The approach used by researchers in this study is qualitative and quantitative. This research uses two kinds of data: primary and secondary data. Researchers obtained preliminary data using interviews, observations, and product assessments by validators, while secondary data were obtained by researchers from books, journals, and previous research thesis. This research was conducted by testing the validity of six validators: two media validators, two language validators, and two material validators. The result of the media expert validity test is 100%, the result of the linguist validity test is 89.42%, and the last result of the material expert validity test is 89.06%, with a final average of 92.82%. So based on the validity test of the thematic interactive multimedia based on PowerPoint conducted by six validators, it showed valid results so that it was feasible to be used in the learning process.